Percepção dolorosa e temperatura cutânea de indivíduos com dor cervical atendidos com fototerapia: ensaio clínico randomizado controlado - Ferreira, Júlia Lacet Silva (2021)
Introduction. Neck pain is a highly prevalent health problem worldwide and there are several physical resources that aim to promote analgesia, including light therapy, such as low-intensity laser therapy and infrared therapy. Although these resources are widely used in physical therapy practice, superiority studies comparing their effects are scarce. Objective: To compare the acute effects of low-power 808nm laser and infrared radiation on pain intensity, pressure-induced pain and skin temperature of the trapezius muscle region in volunteers with subacute and chronic pain. Methods: A clinical trial of superiority, parallel with three arms, randomized, controlled by sham and blinded by the evaluator and the statistician. Pain intensity was evaluated by means of Numerical Scale of Pain, pressure-induced pain threshold, with a pressure dynamometer, and skin temperature of the trapezius region, by IRR, of 91 subjects before (T0), immediately after ( T1), 10 minutes (T2), 20 minutes (T3) and 48 hours (T4) after a phototherapy treatment session. The subjects were randomly allocated into three groups: 1) Laser therapy (GLAS), with laser application in a punctual way (808nm, 0.5J/cm², output power of 10mW); two); Infrared (GINF), with application performed at a distance of 30 cm and an incidence angle of 90º from the trapezius region, for 30 minutes; and 3) Sham (GSHAM), where a punctual laser application was simulated. An analysis of mixed linear models was performed using group interaction terms, time and group-versus-time, considering a first order automatic covariance matrix. All analyzes were performed using SPSS Software, Version 21.0. Results: A significant reduction in intragroup pain intensity was observed in all evaluation times (p <0.05) being the highest reduction in gym after 20 min of intervention with a reduction of 2.38, however, there were no significant intergroup differences in to this outcome. As regards the intensity of pressure pain there was no statistically significant changes between the evaluation times and between the groups. Finally, regarding cutaneous temperature, there was a significant increase only for GINF immediately after the intervention with an average amendment of -2.35 degrees, and this group remained with higher temperature than the GSHAM up to 10 minutes after the intervention. Conclusion: Low-intensity and low-intensity laser therapies Infrared were not more effective than Sham in the treatment of subacute and chronic pain in the trapezius region, nor did they promote significant changes in the regional skin temperature.